Students’ Difficulties in English Writing at Tenth Grade in Senior High School - Doni fransiskus Purba; Sahlan Tampubolon; Erika Sinambela (Institut Agama Islam Negeri Palopo, 2023)
This research discussed about students’ difficulties in writing recount text at tenth grade SMAN 1 Selesai Kab. Langkat. The problem of this research were the students’ difficulties in writing recount text and factors that cause students’ difficulties in writing recount. The objective of this research was to find out the students’ difficulties in writing recount text and to describe the factors that make students have difficulties writing recount text. This research was qualitative descriptive. The source of the data of this research was tenth grade SMAN 1 Selesai Kab. Langkat. Total of the were 24 students. The researcher used test and gave a questionnaire as the instruments. The researcher analysed the data by editing the data, reducing the data, tabulating the data and the last taking conclusion. The researcher found some facts in the field. First, it was found that the answer that students’ difficulties in writing recount text were difficulties in developing the content, organization, vocabulary, language, and mechanics. The data were got from students’ test that had been analysed. Beside that, the causes of the students’ difficulties in writing recount text were grammatical weakness, knowledge and understanding, less practice, and educational background